Rome in Egypt's Eastern Desert : Volume One - Cuvigny, Helene (Book collections on Project MUSE., 2021)
"Rome in Egypt's Eastern Desert collects Prof. Cuvigny's most important articles on Egypt's Eastern desert during the Roman period. From the excavations of the forts that she has directed have come a wealth of material, including tens of thousands of texts written on potsherds (ostraca). Some of these are administrative texts, but many more are correspondence, both official and private, written by and to the people (mostly but not all men) who lived and worked for periods of time in these remote and harsh environments, supported by an elaborate network of defense, administration and supply that tied the entire region together. The contents have all been published earlier in peer-reviewed venues, but almost entirely in French. All contributions have been translated or checked by the editor and brought up to date with respect to bibliography and in some cases significantly rewritten by the author, in order to take account of the enormous amount of new material discovered in the intervening time and subsequent publications. A full index will make this body of work far more accessible than it now is. This book brings together thirty years of detailed study of this material, bringing to life the geography, administration, military, quarry operations, life in the forts, and the religion and expressive language of the population who lived in them"--